Potret Metode Tafsir Ahkam al-Qur’an Karya Abu Bakar al-Jashshash - Alfian Dhany Misbakhuddin; Ahmad Wafi Nur Safaat (Program Magister Ilmu Al-Qur'an dan Tafsir, Fakultas Ushuluddin dan Pemikiran Islam, Universitas Islam Negeri Raden Fatah Palembang, 2022)
This paper attempts to explore the methodology of the interpretation of Ahkam al-Qur’an by Abu Bakr al-Jashshash. The research that uses the descriptive-analytical method results in the conclusion that the book of commentary on the Ahkam al-Qur’an by al-Jashshash is included in the category of bil-Iqitiran interpretation based on the source of its interpretation. Because in interpreting verses about law, al-Jashshash compares the Qur’an, hadith, poetry and reason, so this interpretation deserves to be called tafsir bi al-ra’yi. Meanwhile, al-Jashshash’s method of interpreting the Qur’an is using the ithnaby or tahlili method, because he describes the content of the verse in detail at length and develops it into several problems. For the style of interpretation, because it is in line with the name of the book of interpretation, namely Ahkam al-Qur’an, it is clear that the tendency used by al-Jashshash is the style of fiqhi interpretation.